a)
27: [26+(6×a-7×3): 9]+(13-2×2×3)=2
27: [26+(6×a-21): 9]+(13-4×3)=2
27: [26+(6×a-21): 9]+(13-12)=2
27: [26+(6×a-21): 9]+1=2
27: [26+(6×a-21): 9]=2-1
27: [26+(6×a-21): 9]=1
26+(6×a-21): 9=27:1
26+(6×a-21): 9=27
(6×a-21): 9=27-26
(6×a-21): 9=1
6×a-21=1×9
6×a-21=9
6×a=9+21
6×a=30
a=30:6
a=5
b)
5+[16-(9: a×8+7)]× 6=4: (1×2)+(3×3)
5+[16-(9: a×8+7)]× 6=4: 2+9
5+[16-(9: a×8+7)]× 6=2+9
5+[16-(9: a×8+7)]× 6=11
[16-(9: a×8+7)]× 6=11-5
[16-(9: a×8+7)]× 6=6
16-(9: a×8+7)=6:6
16-(9: a×8+7)=1
9: a×8+7=16-1
9: a×8+7=15
9: a×8=15-7
9: a×8=8
9: a=8:8
9: a=1
a=9:1
a=9